Precolonial citizenship in South Sulawesi. Issue 3 (3rd April 2019) - Henley, David; Caldwell, Ian
ABSTRACT: Citizenship is a difficult concept to apply to non-Western societies. The idea of citizenship has its origins in Ancient Athens and Republican Rome, its modern form having been shaped by the French Revolution and the nationalisms of nineteenth- and twentieth-century Europe. Yet the idea of a social contract between members of a society and their leaders is also found in non-Western societies. The notion of integrated rights and duties of free individuals has existed for centuries among the Bugis and Makasar peoples of South Sulawesi, Indonesia. In this paper, concepts and practices developed by the Bugis and Makasar are compared against Classical Greek and Roman citizenship, and the status of Bugis women is briefly examined. In conclusion, it is argued that an important contractual principle that has its origins in patron-client relations was fundamental to the foundation of the South Sulawesi states and to their economic and social well-being.